La Banda della Magliana nel Romanzo Criminale di De Cataldo - Pisano, Alessandro (Italogramma, 2025)
This study analyzes how Giancarlo De Cataldo's Romanzo Criminale (2002) adapts the real-life events of the Banda della Magliana into a fictionalized narrative. Focusing on the transformation of figures existing in real life and events, the study explores De Cataldo's approach in blending noir fiction with Italy's criminal history, highlighting the gang's rise and fall as a significant aspect of Roman and national political life. Through this lens, the novel reinterprets the criminal story, turning it into a social and political phenomenon.